Probing the amalgam: the relationship between science teachers' content, pedagogical and pedagogical content knowledge - Neumann, Knut; Kind, Vanessa; Harms, Ute (International journal of science education, 2019)
This Special Issue aims to present evidence about the relationships between content knowledge (CK), pedagogical knowledge (PK) and pedagogical content knowledge (PCK); the development of these types of knowledge in novice and experienced secondary science teachers; and how CK, PK and/or PCK impact students' learning. Since Shulman's introduction of PCK as the feature that distinguishes the teacher from the content expert, researchers have attempted to understand, delineate, assess and/or develop the construct in pre- and in-service teachers. Accordingly, empirical findings are presented that permit further discussion. Outcomes permit post-hoc examination of a recent, collectively described, 'consensus' model of PCK, identifying strengths and potential issues. As we will illustrate, the relationship between CK, PK and PCK is central to this; that is, probing the hypothesis of pedagogical content knowledge as an 'amalgam' of content and pedagogical knowledge.